Correlation of Serum Cystatin-C and Creatinine as Predictive Prognostic Markers for Renal Impairment in Pre Eclamptic Patients - Javeria Hameed Shaikh, Khalida Shaikh, Salma Farrukh Memon, Rubina Zareen, Abdul Ghaffor, Urooj Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Renal impairment is becoming more common as adverse effect of preeclampsia in emerging nations. Preeclampsia is a complication of pregnancy that can be prevented by using Cystatin C as a better and earlier renal biomarker than creatinine in order to evaluate the renal function. Method: The study was done on 150 women in the Obstetrics and Gynecology Department at LUMHS Jamshoro, dividing them into three gestational age groups. The ANNOVA test was used to determine if cystatin-c is a superior marker to serum creatinine. SPSS version 21 was used to analyze the data without any dropout of the patients. Results: In this study, one hundred fifty (150) pre eclamptic pregnant women in the 20–35-year-old age range were chosen. The cystatin-c level was 1.2 ± 0.7 at 36th weeks of gestation in the forty of the patients of age 20-25, while creatinine was 1 ± 0.7. In sixty-eight (68) patients of age between 25-30 years, cystatin-c levels ranged from 1.6 ± 0.8 ng/mL, while creatinine levels ranged from 1.1 ± 0.9 ng/mL. In patients above > 30 years’ age group, the serum cystatin C level was found to be 1.9 ± 0.8, while the creatinine level was found to be 1.2±0.6 at 36th week of gestation. Conclusion: This research shows that cystatin C levels rise early and proved to be a better predictor of renal problems as compared to serum creatinine, which didn't increase considerably. Keywords: Cystatin-C, Preeclampsia, kidney impairment